2020
DOI: 10.1109/tns.2020.3019887
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of the CLICTD Pixelated Monolithic Sensor Chip

Abstract: A novel monolithic pixelated sensor and readout chip, the CLIC Tracker Detector (CLICTD) chip, is presented. The CLICTD chip was designed targeting the requirements of the silicon tracker development for the experiment at the Compact Linear Collider (CLIC), and has been fabricated in a modified 180 nm CMOS imaging process with charge collection on a high-resistivity p-type epitaxial layer. The chip features a matrix of 16×128 elongated channels, each measuring 300×30 µm 2. Each channel contains 8 equidistant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…In addition, the sub-pixel segmentation scheme of the front-end has shown to deliver the required accuracy while minimizing the digital footprint. Previous results have shown that the estimated powerconsumption [10] as well as the material budget [14] also comply with the requirements.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In addition, the sub-pixel segmentation scheme of the front-end has shown to deliver the required accuracy while minimizing the digital footprint. Previous results have shown that the estimated powerconsumption [10] as well as the material budget [14] also comply with the requirements.…”
Section: Discussionsupporting
confidence: 58%
“…In the following, the sensor and readout design are outlined. A detailed description is presented elsewhere [10].…”
Section: The Clictd Monolithic Sensormentioning
confidence: 99%
See 2 more Smart Citations
“…The continuous n-implant design is used for the CLIC Tracker Detector (CLICTD) sensor, a technology demonstrator developed in the context of the tracking detector studies for the Compact Linear Collider (CLIC) [8].…”
Section: Sensor Designmentioning
confidence: 99%